Neutrophils in Type 1 Diabetes: Untangling the Intricate Web of Pathways and Hypothesis - Laura Nigi; Erika Pedace; Francesco Dotta; Guido Sebastiani (Biomolecules)
Neutrophils are increasingly recognized as key contributors to the pathogenesis of Type 1 Diabetes (T1D), yet their precise mechanistic role in disease onset and progression remains incompletely understood. While these innate immune cells reside in pancreatic tissue and support tissue homeostasis under physiological conditions, they can also drive tissue damage by triggering innate immune responses and modulating inflammation. Within the inflammatory milieu, neutrophils establish complex, bidirectional interactions with various immune cells, including macrophages, dendritic cells, natural killer cells, and lymphocytes. Once activated, they may enhance the innate immune response through direct or indirect crosstalk with immune cells, antigen presentation, and β-cell destruction or dysfunction. These mechanisms underscore the multifaceted and dynamic role of neutrophils in T1D, shaped by their intricate immunological interactions. Further research into the diverse functional capabilities of neutrophils is crucial for uncovering novel aspects of their involvement in T1D, potentially revealing new therapeutic targets to modulate disease progression.